Cementing material capable of overcoming Zn < 2 + > and Cu < 2 + > and delaying cement hydration and early strength development and preparation method

By adding nano-C-S-H gel to cement clinker, the problems of delayed cement hydration and early strength development caused by heavy metals zinc and copper are solved, and the early strength and setting time of cement are significantly improved.

CN119330615APending Publication Date: 2025-01-21SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411630838.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The presence of heavy metals zinc and copper in cement-based materials leads to delayed cement hydration and early development, affecting the performance of cement-based materials.

Method used

By adding nano-C-S-H gel to cement clinker, the hydration process is improved and the slurry structure is optimized to overcome the inhibitory effects of Zn2+ and Cu2+.

Benefits of technology

It significantly improves the early strength of cement clinker containing heavy metals zinc and copper, shortens the setting time, optimizes the composition of hydration products, and improves the slurry structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330615A_ABST
    Figure CN119330615A_ABST
Patent Text Reader

Abstract

The invention discloses a cementing material capable of overcoming Zn < 2 + > and Cu < 2 + > and delaying cement hydration and early strength development and a preparation method of the cementing material. The cementing material comprises the following substances in percentage by mass: 95-97% of clinker containing heavy metals, 1-2% of nano C-S-H gel and the balance of gypsum, the total zinc content in the clinker containing heavy metals is greater than 500mg / kg; the total copper content is greater than 600mg / kg; based on the synergistic effect of the whole chemical components of the heavy metal-containing clinker and the composite auxiliary cementing material, the hydration process and the slurry structure are changed to overcome Zn < 2 + > and Cu < 2 + >, and cement hydration and early strength development are delayed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite gelling material and a preparation method thereof, in particular to a composite gelling material which overcomes Zn 2+ , Cu 2+ A cementitious material for delaying cement hydration and early strength development and a preparation method thereof. Background Art

[0002] With the continuous progress of industrialization and modernization, frequent human activities such as mining, smelting, and coal burning have produced a large amount of industrial hazardous waste, domestic garbage, waste residue, sludge, etc. rich in toxic heavy metal ions. These solid wastes can be added to cement production as alternative raw materials or fuels through cement kiln co-disposal technology for resource utilization or harmless treatment. However, a large amount of harmful heavy metals contained in these solid wastes will remain in the cement clinker, and in the subsequent use of cement clinker, heavy metals will interact with the mineral phase in the cement clinker in the form of ions, affecting the hydration process of cement clinker, and then affecting the various properties of cement-based materials.

[0003] Cement clinker obtained through cement kiln co-processing contains a variety of heavy metals, among which the content of heavy metal zinc and heavy metal copper is relatively high. Due to the presence of heavy metal zinc and heavy metal copper, during the use of cement clinker, heavy metal zinc and heavy metal copper will form a difficult-to-dissolve film on the surface of cement clinker particles, seriously hindering the hydration process of cement. It has a serious impact on the working performance and mechanical properties of cement-based materials. Summary of the invention

[0004] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for overcoming the deficiencies in the prior art. 2+ , Cu 2+ A cementitious material for delaying cement hydration and early strength development and a preparation method thereof.

[0005] Technical solution: A method to overcome Zn 2+ , Cu 2+ A cementitious material for delaying cement hydration and early strength development and a preparation method thereof, comprising the following substances in percentage by mass: 95wt.% to 97wt.% of heavy metal-containing clinker, 1wt.% to 2wt.% of nano CSH gel, and the remainder being gypsum; the total zinc content of the heavy metal-containing clinker is greater than 500mg / kg; the total copper content is greater than 600mg / kg;

[0006] The nano-CSH gel is prepared by using a dispersant, a silicene aqueous solution, a soluble calcium salt and a soluble silicon salt.

[0007] Furthermore, the gypsum is any one of desulfurized gypsum, phosphogypsum and fluorinated gypsum.

[0008] The above method overcomes Zn 2+, Cu 2+ The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0009] Step 1: weigh the required clinker, auxiliary cementitious material, heavy metal salt and gypsum, and stir and mix them evenly;

[0010] Step 2: Weigh room temperature water according to a water-cement ratio of 0.4 to 0.5, slowly add the room temperature water to the mixture obtained in step 1, stir slowly and then switch to high shear mode for high-speed stirring to form a plastic cementitious material slurry, pour it into a mold, and cure it at room temperature;

[0011] Step 3: After the mold is removed, the test block is cured in a specific humidity environment for 28 days.

[0012] Furthermore, in step 1, the stirring time is 4 to 5 minutes.

[0013] Furthermore, in step 2, the speed of slow stirring is 120 r / min to 160 r / min, the time is 120 s to 150 s, the speed of high-speed stirring is 280 r / min to 300 r / min, the time is 120 s to 150 s. The time of normal temperature curing is 24 h to 36 h.

[0014] Furthermore, in step three, the constant humidity environment is a water-free environment with a humidity not less than 90%.

[0015] Preparation principle: Heavy metal zinc and heavy metal copper are in the high alkaline environment provided by cement-based materials. 2+ and Cu 2+ Will be with OH - The ions form an insoluble film on the surface of cement clinker particles, changing the composition of the hydration products and seriously hindering the hydration process of cement. 2+ , Cu 2+ It will interact with CaO to some extent, consuming some Ca 2+ , which will cause the Ca / Al ratio in the cement paste pore solution to decrease. This will further affect the formation of C3AH6 and affect the performance of cement-based materials. Therefore, the present invention improves the hydration process and optimizes the slurry structure by adding nano CSH gel, thus overcoming the problem of Zn 2+ , Cu 2+ Delaying cement hydration and early strength development.

[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0017] 1. Based on the influence mechanism of heavy metal zinc and heavy metal copper on cement hydration, a nano-CSH gel component with the ability to adsorb divalent ions is introduced;

[0018] 2. Because heavy metal zinc and heavy metal copper will react with OH - The ions react, resulting in almost no calcium hydroxide in the early hydration products, reducing the strength. The addition of nano-CSH gel changes the type of hydration products, causing calcium hydroxide to reappear in the early stage;

[0019] 3. The addition of nano-CSH gel generates more silicon-aluminum phases in the hydration product, fills the voids, optimizes the slurry structure, and helps improve the strength in the later stage;

[0020] 4. The present invention can significantly improve the early strength of cement clinker containing heavy metal zinc and heavy metal copper by adding a relatively low content of nano CSH gel, thereby controlling the cost while ensuring the strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the nano CSH gel prepared by the present invention overcoming the inhibitory effect of heavy metals;

[0022] Figure 2 It is a schematic diagram of the bonding mechanism of heavy metal ions prepared by the present invention;

[0023] Figure 3 is the XRD diagram of the hydration product of the cement-based material prepared by the present invention;

[0024] Figure 4 is the setting time of the cement-based material prepared by the present invention;

[0025] Figure 5 It is the compressive strength of the cement-based material specimen prepared by the present invention. DETAILED DESCRIPTION

[0026] In the embodiment, 52.5 grade silicate clinker was mixed with 3 wt.% of zinc nitrate and copper nitrate (providing Zn(II) and Cu(II)) to simulate high heavy metal content clinker. The 52.5 grade silicate clinker used met the requirements of GB 30760 "Technical Specifications for Co-disposal of Solid Wastes in Cement Kilns".

[0027] In the following embodiments, the heavy metal content of the clinker is much higher than the requirements of GB 30760 "Technical Specifications for Co-treatment of Solid Wastes in Cement Kilns" by adding zinc nitrate and copper nitrate (providing Zn(II) and Cu(II)), which is approximately 30 times and 100 times higher than the maximum value of "heavy metal content limit in cement clinker" (zinc: 500 mg / kg; copper: 100 mg / kg).

[0028] Example 1

[0029] A method to overcome Zn 2+ , Cu 2+The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0030] Step 1: weigh 93g of heavy metal-containing clinker, 3g of zinc salt, 1g of nano CSH gel, and 3g of gypsum, and stir for 1 minute to evenly mix them together. The gypsum is desulfurized gypsum.

[0031] Step 2: Weigh room temperature water according to a water-cement ratio of 0.5, slowly add the water to the material obtained in step 1, slowly stir at 150 r / min in a mixer for 120 seconds, and then stir at a high speed of 290 r / min for 120 seconds in a high shear mode to form a plastic composite cementitious material slurry, pour it into a mold, and cure it at room temperature for 36 hours.

[0032] Step 3: After the mold is removed, the specimen is cured in a water-free environment with a humidity of not less than 90% for 28 days.

[0033] Example 2

[0034] A method to overcome Zn 2+ , Cu 2+ The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0035] Step 1: weigh 92.5g of heavy metal-containing clinker, 3g of zinc salt, 1.5g of nano CSH gel, and 3g of gypsum, and stir for 1 minute to evenly mix them together. The gypsum is desulfurized gypsum.

[0036] Step 2: Weigh room temperature water according to a water-cement ratio of 0.5, slowly add the water to the material obtained in step 1, slowly stir at 150 r / min in a mixer for 120 seconds, and then stir at a high speed of 290 r / min for 120 seconds in a high shear mode to form a plastic composite cementitious material slurry, pour it into a mold, and cure it at room temperature for 36 hours.

[0037] Step 3: After the mold is removed, the specimen is cured in a water-free environment with a humidity of not less than 90% for 28 days.

[0038] Example 3

[0039] A method to overcome Zn 2+ , Cu 2+ The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0040] Step 1: weigh 92g of heavy metal-containing clinker, 3g of zinc salt, 2g of nano CSH gel, and 3g of gypsum, and stir for 1 minute to evenly mix them together. The gypsum is desulfurized gypsum.

[0041] Step 2: Weigh room temperature water according to a water-cement ratio of 0.5, slowly add the water to the material obtained in step 1, slowly stir at 150 r / min in a mixer for 120 seconds, and then stir at a high speed of 290 r / min for 120 seconds in a high shear mode to form a plastic composite cementitious material slurry, pour it into a mold, and cure it at room temperature for 36 hours.

[0042] Step 3: After the mold is removed, the specimen is cured in a water-free environment with a humidity of not less than 90% for 28 days.

[0043] Example 4

[0044] A method to overcome Zn 2+ , Cu 2+ The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0045] Step 1: weigh 93g of heavy metal-containing clinker, 3g of zinc salt, 1g of nano CSH gel, and 3g of gypsum, and stir for 1 minute to evenly mix them together. The gypsum is desulfurized gypsum.

[0046] Step 2: Weigh room temperature water according to a water-cement ratio of 0.5, slowly add the water to the material obtained in step 1, slowly stir at 150 r / min in a mixer for 120 seconds, and then stir at a high speed of 290 r / min for 120 seconds in a high shear mode to form a plastic composite cementitious material slurry, pour it into a mold, and cure it at room temperature for 36 hours.

[0047] Step 3: After the mold is removed, the specimen is cured in a water-free environment with a humidity of not less than 90% for 28 days.

[0048] Example 5

[0049] A method to overcome Zn 2+ , Cu 2+ The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0050] Step 1: weigh 92.5g of heavy metal-containing clinker, 3g of copper salt, 1.5g of nano CSH gel, and 3g of gypsum, and stir for 1 minute to evenly mix them together. The gypsum is desulfurized gypsum.

[0051] Step 2: Weigh room temperature water according to a water-cement ratio of 0.5, slowly add the water to the material obtained in step 1, slowly stir at 150 r / min in a mixer for 120 seconds, and then stir at a high speed of 290 r / min for 120 seconds in a high shear mode to form a plastic composite cementitious material slurry, pour it into a mold, and cure it at room temperature for 36 hours.

[0052] Step 3: After the mold is removed, the specimen is cured in a water-free environment with a humidity of not less than 90% for 28 days.

[0053] Example 6

[0054] A method to overcome Zn 2+ , Cu 2+ The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0055] Step 1: weigh 92g of heavy metal-containing clinker, 3g of copper salt, 2g of nano CSH gel, and 3g of gypsum, and stir for 1 minute to evenly mix them together. The gypsum is desulfurized gypsum.

[0056] Step 2: Weigh room temperature water according to a water-cement ratio of 0.5, slowly add the water to the material obtained in step 1, slowly stir at 150 r / min in a mixer for 120 seconds, and then stir at a high speed of 290 r / min for 120 seconds in a high shear mode to form a plastic composite cementitious material slurry, pour it into a mold, and cure it at room temperature for 36 hours.

[0057] Step 3: After the mold is removed, the specimen is cured in a water-free environment with a humidity of not less than 90% for 28 days.

[0058] Comparative Example 1

[0059] A method to overcome Zn 2+ , Cu 2+ The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0060] Step 1: weigh 97g of heavy metal-containing clinker and 3g of gypsum, and stir for 1 minute to evenly mix them together. The gypsum is desulfurized gypsum.

[0061] Step 2: Weigh room temperature water according to a water-cement ratio of 0.5, slowly add the water to the material obtained in step 1, slowly stir at 150 r / min in a mixer for 120 seconds, and then stir at a high speed of 290 r / min for 120 seconds in a high shear mode to form a plastic composite cementitious material slurry, pour it into a mold, and cure it at room temperature for 36 hours.

[0062] Step 3: After the mold is removed, the specimen is cured in a water-free environment with a humidity of not less than 90% for 28 days.

[0063] Comparative Example 2

[0064] A method to overcome Zn 2+ , Cu 2+ The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0065] Step 1: weigh 94g of heavy metal-containing clinker, 3g of zinc salt, and 3g of gypsum, and stir for 1 minute to evenly mix them together. The gypsum is desulfurized gypsum.

[0066] Step 2: Weigh room temperature water according to a water-cement ratio of 0.5, slowly add the water to the material obtained in step 1, slowly stir at 150 r / min in a mixer for 120 seconds, and then stir at a high speed of 290 r / min for 120 seconds in a high shear mode to form a plastic composite cementitious material slurry, pour it into a mold, and cure it at room temperature for 36 hours.

[0067] Step 3: After the mold is removed, the specimen is cured in a water-free environment with a humidity of not less than 90% for 28 days.

[0068] Comparative Example 3

[0069] A method to overcome Zn 2+ , Cu 2+ The preparation method of the composite cementitious material for delaying cement hydration and early strength development comprises the following steps:

[0070] Step 1: weigh 92g of heavy metal-containing clinker, 3g of copper salt, and 3g of gypsum, and stir for 1 minute to evenly mix them together. The gypsum is desulfurized gypsum.

[0071] Step 2: Weigh room temperature water according to a water-cement ratio of 0.5, slowly add the water to the material obtained in step 1, slowly stir at 150 r / min in a mixer for 120 seconds, and then stir at a high speed of 290 r / min for 120 seconds in a high shear mode to form a plastic composite cementitious material slurry, pour it into a mold, and cure it at room temperature for 36 hours.

[0072] Step 3: After the mold is removed, the specimen is cured in a water-free environment with a humidity of not less than 90% for 28 days.

[0073] Table 1 Composition ratios of various formulas and related test results of the embodiments and comparative examples (water-cement ratio 0.50) The compressive strength test and hydration product composition analysis of the cured heavy metal composite cementitious material were carried out.

[0074]

[0075] The compressive strength test method refers to GB / T 17671 "Test method for strength of cement mortar (ISO method)".

[0076] It can be seen from Table 1 that the heavy metal Zn 2+ , Cu 2+ It will significantly reduce the early strength of clinker and seriously delay the setting time of cement-based materials. 2+ , Cu 2+The cement-based material only generates AFt in the early stage, contains a large amount of unhydrated cement clinker, and has a loose slurry structure, which seriously affects its early strength. Analysis of Examples 1, 2, 3 and Examples 4, 5, and 6 found that the addition of nano-CSH gel can significantly increase the content of heavy metal Zn 2+ , Cu 2+ The early strength of the clinker and the shortening of its setting time are shown in Table 2. The results of the analysis of Example 2 and Example 3 and Example 5 and Example 6 show that the effect is similar with the increase of the amount of nano-CSH gel added. The XRD analysis of the hydration products of the corresponding groups shows that no hydration product calcium hydroxide is formed in the early stage of Comparative Example 2 and Comparative Example 3, and the additional generation of heavy metal salts inhibits the hydration process of cement-based materials. The SEM images show that the heavy metal Zn 2+ , Cu 2+ The addition of nano-CSH gel failed to form calcium hydroxide products in the early stage, and the corresponding hydration products were all AFt, resulting in a serious reduction in its early strength. Analysis of the hydration products of Example 2 and Example 5 found that with the addition of nano-CSH gel, the hydration product calcium hydroxide was regenerated and the heavy metal salts no longer existed. From the SEM spectrum, it was found that the corresponding hydration products, the addition of nano-CSH gel on the surface improved the heavy metal Zn 2+ , Cu 2+ The hydration process of clinker optimizes the slurry structure and overcomes the Zn 2+ , Cu 2+ Requirements for delaying cement hydration and early strength development. Figure 1 It shows that a large amount of CSH gel is generated on the surface of C3S clinker without adding divalent heavy metals; after adding divalent heavy metals, a heavy metal product film is generated on the surface to inhibit the hydration of C3S; after adding nano-CSH seeds, a heavy metal-containing CSH gel product is generated. Figure 2 Infrared spectra show that heavy metal ions exist in cement-based materials in the form of ionic bonding. Among the above embodiments, the best embodiments are Embodiment 2 and Embodiment 5, which have setting time that meets the requirements of the specification and high compressive strength.

[0077] It should also be noted that although the embodiments and comparative examples were tested by simulating high heavy metal content clinker by adding heavy metal salts, the high heavy metal content clinker actually produced does not exceed the limit specified by national standards because it is calcined and solidified.

Claims

1. A method to overcome Zn 2+ , Cu 2+ Cementitious material that delays cement hydration and early strength development, characterized by: The invention comprises the following substances in mass percentage: 95wt.%-97wt.% of heavy metal-containing clinker, 1wt.%-2wt.% of nano CSH gel, and the rest is gypsum; the total zinc content in the heavy metal-containing clinker is greater than 500mg / kg, and the total copper content is greater than 600mg / kg.

2. A method of overcoming Zn according to claim 1 2+ , Cu 2+ Cementitious material that delays cement hydration and early strength development, characterized by: The nano CSH gel is prepared from a dispersant, a silicene aqueous solution, a soluble calcium salt and a soluble silicon salt.

3. A method of overcoming Zn according to claim 1 2+ , Cu 2+ Cementitious material that delays cement hydration and early strength development, characterized by: The gypsum is any one of desulfurized gypsum, phosphogypsum or fluorinated gypsum.

4. A method of overcoming Zn as claimed in any one of claims 1 to 3 2+ , Cu 2+ The preparation method of a cementitious material for delaying cement hydration and early strength development is characterized in that: The following steps are involved: Step 1, weigh the required clinker, nano CSH gel auxiliary gelling material, heavy metal salt, and gypsum, and stir and mix them evenly; Step 2: Weigh room temperature water according to a water-cement ratio of 0.4 to 0.5, slowly add the room temperature water to the mixture obtained in step 1, stir slowly and then switch to high shear mode for high-speed stirring to form a plastic cementitious material slurry, pour it into a mold, and cure it at room temperature; Step 3: After the mold is removed, the test block is cured in a specific humidity environment for 28 days.

5. A method of overcoming Zn according to claim 4 2+ , Cu 2+ The preparation method of a cementitious material for delaying cement hydration and early strength development is characterized by: The stirring time in step 1 is 4 to 5 minutes.

6. A method according to claim 4 to overcome Zn 2+ , Cu 2+ The preparation method of a cementitious material for delaying cement hydration and early strength development is characterized by: The amount of heavy metal salt added in step 1 is 1 wt.% to 3 wt.%.

7. A method of overcoming Zn according to claim 4 2+ , Cu 2+ The preparation method of a cementitious material for delaying cement hydration and early strength development is characterized by: The heavy metal salt in step 1 is one or two of copper salt and zinc salt or other soluble divalent heavy metal salts such as manganese.

8. A method according to claim 4 to overcome Zn 2+ , Cu 2+ The preparation method of a cementitious material for delaying cement hydration and early strength development is characterized by: In step 2, the speed of slow stirring is 120r / min~160r / min, the time is 120s~150s, and the speed of high-speed stirring is 280r / min~300r / min, the time is 120s~150s.

9. A method according to claim 4 to overcome Zn 2+ , Cu 2+ The preparation method of a cementitious material for delaying cement hydration and early strength development is characterized by: In the step 2, the time of normal temperature curing is 24h to 36h.

10. A method according to claim 4 to overcome Zn 2+ , Cu 2+ The preparation method of a cementitious material for delaying cement hydration and early strength development is characterized by: In the step 3, the specific humidity environment is a water-free environment with a humidity not less than 90%.